Growth Modes of Ice Crystals in Supercooled Water and Aqueous Solutions - Pruppacher, H. R. (Journal of Glaciology, 1967)
The growth modes of ice crystals in supercooled water and various aqueous solutions were studied at different supercoolings by a motion-picture technique. ln pure water contained in plastic capillary tubes, ice dendrites formed which at supercoolings between 1 and 4°C. grew parallel to the tube axis. At supercoolings larger than 4°C. the direction of growth was inclined to the tube axis such that the dendrites hit the tube wall and afterwards proceeded growing in a new direction. As a result it appeared that the ice crystals grew in a zig-zag or screw fashion. This growth mode became enhanced when the supercooling was increased or salts were dissolved in the water. In large water drops, ice dendrites formed which at supercoolings smaller than 1°C. were co-planar with the seed crystal and between 1° and 5°C. split into two dendritic segments. At supercoolings larger than 5°C. multiple splitting of the seed crystal was observed and this became strongly enhanced when salts were dissolved in the water. Tentative explanations for these results are given.